Circadian chronotypes and their effect on athletic performance: a systematic review - Maheshwari, D.; Singla, D.; Malhotra, D.; Zutshi, K. (Sport Sciences for Health, 2022)
Introduction The individual differences in exogenous and endogenous factors influence the various physiological and psychological processes related to athletic performance. The chronotypes reflect innate variation, which is essential to consider for obtaining significant outcomes in sports competitions and optimizing adequate recovery during rehabilitation following an injury. This systematic review aims to investigate the effect of chronotypes on athletic performance in the athletic population.